2003
DOI: 10.1002/ptr.1333
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of the antimicrobial property of Polyalthia longifolia var. pendula: isolation of a lactone as the active antibacterial agent from the ethanol extract of the stem

Abstract: Bioassay guided fractionation of the ethanolic extract of Polyalthia longifolia var. pendula stem, which showed promising antibacterial activity against thirteen Gram-positive and nine Gram-negative organisms, furnished (3S,4R)-3,4,5-trihydroxypentanoic acid-1,4-lactone (1) as the active principle. The structure of (1) was established by UV, IR, mass, 1H and 13C NMR as well as 2D NMR spectral studies and the formation of its acetate (1a). On acetylation activity of (1) was markedly reduced. It is synthetically… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
31
0

Year Published

2005
2005
2015
2015

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 38 publications
(31 citation statements)
references
References 21 publications
0
31
0
Order By: Relevance
“…Biological evaluation of the plant has resulted in the isolation of diterpenes and alkaloids which have been reported to be cytotoxic against human cancer cell lines (Chen et al, 2000) and to possess antimicrobial (Ferdous et al, 1992;Rashid et al, 1996) activity. Recently, a lactone with promising antibacterial activity has been isolated from the stem (Faizi et al, 2003). The present study shows that P. longifolia var.…”
Section: Introductionmentioning
confidence: 88%
“…Biological evaluation of the plant has resulted in the isolation of diterpenes and alkaloids which have been reported to be cytotoxic against human cancer cell lines (Chen et al, 2000) and to possess antimicrobial (Ferdous et al, 1992;Rashid et al, 1996) activity. Recently, a lactone with promising antibacterial activity has been isolated from the stem (Faizi et al, 2003). The present study shows that P. longifolia var.…”
Section: Introductionmentioning
confidence: 88%
“…pendula (Annonaceae) is a tall evergreen tree cultivated all over India. The plant has been used in the traditional system of medicine for the treatment of fever, skin diseases, hypertension (Kirtikar & Basu, 1995), hepatoprotective, anti-inflammatory (Tanna et al, 2009), antimicrobial (Faizi et al, 2003;Murthy et al, 2005;Nair & Chanda, 2006), hypoglycemic and antihyperglycemic (Nair et al, 2007) and antiulcer activities (Malairajan et al, 2008). Polyalthia cerasoides (Roxb.)…”
Section: Research Articlementioning
confidence: 99%
“…pendula has been less investigated compared with P. longifolia (Chen et al, 2000;Hara et al, 1995). Recent studies on its stem, roots, root bark and their isolates showed excellent antibacterial potency (Faizi et al, 2000(Faizi et al, , 2003a(Faizi et al, , 2003b) and significant hypotensive activity (Faizi et al, 2005).…”
Section: Introductionmentioning
confidence: 97%